Self-Regulated Learning Skills of ELT Pre-Service Teachers during Post-Earthquake Emergency Remote Education in Türkiye - Akyıldız, Seçil Tümen; Cig, Oguzcan; Çelik, Vildan (My University, 2023)
The devastating earthquake that struck southern Türkiye has challenged teaching and learning, as in the COVID-19 pandemic, since a rapid transition from face-to-face education to emergency remote education occurred in higher education institutions. The shift to post-earthquake emergency remote education (PERE) has also posed challenges to college students' self-regulated learning skills (SRLS). This issue has also affected students enrolled in certain programs, such as English Language Teaching (ELT). Therefore, this study aims to investigate ELT pre-service teachers’ views on the use of SRLS during the PERE period. The methodology in this research is a semi-structured interview carried out through focus group discussion and included eight junior ELT pre-service teachers at a university in the Black Sea Region in Türkiye. The researchers conducted the interview via Zoom, and qualitative content analysis was used to examine the data. The findings revealed that the majority employed SRLS efficiently in face-to-face education and even in pandemic-driven remote education, and they found it hard to achieve the same level of performance during PERE. They are not fully behaviorally, metacognitively, and motivationally self-regulated learners in PERE. The findings, thus, suggest that motivational factors, psychological distress, and the issues that cause emergency remote education can affect the effective implementation of self-regulated learning (SRL). Hopefully, this research will contribute to understanding ELT pre-service teachers’ SRLS during emergency remote education launched after a natural disaster, as a relatively small body of literature is concerned with emergency remote education processes after a natural disaster.
Keywords: English Language Teaching (ELT); Pre-service Teachers; Natural Disaster; Emergency Remote Education; Self-regulated Learning Skill